A behaviourally-informed app can encourage switching of financial products - Deirdre Robertson; Olga Poluektova; Ciarán Lavin; Shane Timmons; Pete Lunn (The Economic and Social Research Institute (ESRI), 2024)
Customers who have financial products (e.g., bank accounts, loans, credit cards and mortgages) are unlikely to change to another provider or change the terms of the product within the same provider (i.e., to "switch"). Significant monetary gains can be made by switching, but switching rates tend to hover at only around 2-5% per year. Some of the reasons why consumers do not switch can be summarised as insensitivity to differences in seemingly small bank charges and interest rates, administrative burdens, and lack of previous experience that can be helpful in good habit adoption. Some work has shown that behavioural interventions can increase switching rates, but not by a large amount. Many of the behavioural interventions tested have either been informational, informing consumers that switching is an option, or changes to the choice architecture. However, diagnostic work on what predicts consumer switching behaviour suggests that past shopping around behaviour is the strongest predictor of switching. Interventions that target increased sensitivity to interest rate differences and build experience of some of the behaviours that are precedents to switching may be more effective. This paper reports the results of a randomised controlled field trial to test a behaviourally informed app designed to encourage switching. The app was designed following a nationally representative diagnostic survey of switching behaviours and two pilot trials. It was then tested in a sample of 1,239 consumers over 5 months. The app doubled the number of financial products being switched over the trial period. It also substantially increased the number of participants visiting comparison websites. The app did not increase comprehension, confidence or self-reported knowledge suggesting that it did not act purely as an informational intervention but may instead have acted as a type of behavioural rehearsal. Even if improved, any app will not dramatically increase switching rates. The overall numbers of switchers were still low, with only 2% of products being switched in the intervention. Yet the relative effect of the app on behaviour is far larger than previous nudge-style interventions to encourage switching. It was also carried out over a relatively short period of time. The effect of the app on visits to comparison websites may have future benefits as shopping around predicts future switching. In sum, the behaviourally informed app tested in this trial successfully increased real switching behaviour in a large sample of consumers in Ireland.
Keywords: 330; Financial product; Switching behavior; Mobile application; Ireland; Finanzprodukt; Wechselverhalten; Mobile Anwendung; Irland